Principal components for Community Strength Support : A Case Study of Communities in Nonthaburi - ฉายรัศมีกุล, วสันต์ (Journal of Yanasangvorn Research Institute Mahamakut Buddhist University, 2018)
The objective of this research was to study the principal components of the community strength support: a case study of communities in Nonthaburi. There are 1,193,711 populations who live in Nonthaburi. The sample size that was determined 20 times of variables consisted of 500 samples who were gathered the data from the accidental selection according to the proportions of each sample for each sub-district in Nonthaburi. The research instrument was the questionnaire with the total reliability at .932. The statistics was analyzed by Exploratory Factor Analysis. The finding of this research was revealed that there are six principal components of the community strength support in Nonthaburi: the first component was social component, the second component was community leader, the third component was community participation, the fourth component was self-reliant ability, the fifth component was human relations of people in the community, and the six components was potentiality of people in the community